The Impact Toughness and Hardness of Treated and Untreated Sisal Fibre-Epoxy Resin Composites - Wilson Webo; Leonard Masu; Maina Maringa (Advances in Materials Science and Engineering)
The effect of the combined chemical treatment of sisal fibres through the subsequent processes of mercerisation (alkali treatment), then silane treatment and eventually acid hydrolysis, on sisal fibre was investigated. The effect of the treated fibres on the impact toughness and hardness of their composites with epoxy resin was also studied. Scanning electron microscopy of the surfaces of the treated and untreated fibres showed that the chemical treatment processes enhanced the removal of surface impurities and therefore increased the roughness of the surfaces of the fibres. This avails an increased surface area for interlocking with matrix and is, therefore, expected to enhance adhesion of the two. The treated fibre reinforced composites were observed to have higher values of impact toughness and hardness than the untreated fibre reinforced composites. These higher values were attributed to better interfacial bonding due to better mechanical interlocking between the treated fibres and epoxy resin arising from the increased roughness of the treated fibres.